Implementing Cooperative Learning in Indonesian Language Instruction: A Case Study on Explanatory Texts in Secondary Education - Yandeka Putri Meilani; Henry Friantary (JPI: Jurnal Pustaka Indonesia, 2023)
This study examines how cooperative learning (CL) is implemented in teaching explanatory texts at MTs Al-Qur’an Harsallakum (grade VIII D) and identifies its supporting/inhibiting factors alongside practical recommendations.The research method used a descriptive qualitative case study design based on a classroom, with one Indonesian language teacher and 23 purposively selected students participating. Data were collected over approximately one month through non-participant observation at two core meetings, semi-structured interviews (teacher and one subsample of students), and document analysis (lesson plans, worksheets/presentations, assessment records). Trustworthiness was ensured through source-method-time triangulation and a documented audit trail. The study showed that the six stages of cooperative learning (CL) were enacted consistently and aligned with the rhetorical demands of explanatory texts, raising student engagement through richer discussions, peer clarification, and group presentations that preserved individual accountability. Supporting conditions included teacher professionalism, purposeful classroom management, and strong student enthusiasm, while scarce reading materials, unstable internet, and uneven post-pandemic readiness inhibited depth and equity. Overall, CL functions as an effective genre-based literacy approach when positive interdependence and individual accountability are explicitly mapped to the explanatory-text structure and supported by a print-rich environment and consistent recognition. Accordingly, we recommend genre-aligned task design, systematic role rotation, dual (group–individual) rubrics, and strengthened learning resources and infrastructure.